PENGARUH RAGI TEMPE DAN FERMENTASI JAGUNG TERHADAP SIFAT ORGANOLEPTIK DAN FISIKOKIMIA FORMULA MP-ASI DENGAN TEPUNG TEMPE - Setyani, Sri; Riana Sari, Noventi; Kuswandari, Eni; Yuliana, Neti (Jurnal Teknologi & Industri Hasil Pertanian, 2013)
The objectives of this research were to investigate the effect of tempeh yeast concentration and fermentation time of corn on organoleptic and physicochemical properties of complementary feeding formula with tempeh flour. The other objective was to obtain the concentration of tempeh yeast and fermentation time of corn starch for the formula of complementary feeding with tempeh flour that produces the best organoleptic and physicochemical properties. This study used a Complete Randomized Design (RAKL) with two factors and five replications. The first factor was the concentration of tempeh yeast that consists of 2 levels (2% and 3%) while the second factor was the length of fermentation which consists of 2 standard (48 hours and 72 hours). Data were analyzed using ANOVA and used LSD test of 5% level of significance. The organoleptic properties observed were; texture, flavor, color, and taste, whereas the physicochemical properties observed were foaming capacity and viscosity. The results showed that the concentration of tempeh yeast and fermentation time of corn gave a significant effect on texture and flavor, but gave no significant effect on the color, taste, foaming capacity and viscocity of complementary feeding. The treatment which had the best organoleptic and physicochemical properties was the treateament using tempeh yeast concentration of 3% and fermentation time of 48 hours with an average value of 3,19 colors (amber), 2,86 aroma (neutral), 3,14 texture (medium), 2,64 sense (neutral), 2,12% foaming and viscosity of 9,50 BU Key words: complementary feeding (MP-ASI), fermented corn flour, tempeh flour.